Synthesis and characterization of hydroxyapatite-nanosilver-clove oil (Eugenia Caryophyllus) as antibacterial in toothpaste preparations against streptococcus mutans bacteria - Browi Nugroho; Sari Edi Cahyaningrum (Jurnal Pijar Mipa, 2023)
The formation of dental caries results from the activity of Streptococcus mutans bacteria. One of the efforts to prevent dental caries is using toothpaste containing antibacterial compounds such as hydroxyapatite-nanosilver-clove oil. This study aims to synthesize and characterize hydroxyapatite-nanosilver-cloves oil as an antibacterial that causes dental caries. In this study, physical properties were tested, namely, particle size with PSA, spreadability, stickiness, homogeneity, and chemical properties tested in functional groups with FTIR, pH, and antibacterial activity with the disc diffusion method. This study used 2% hydroxyapatite, ten ppm nanosilver, tween 80, xanthan gum, 70% sorbitol, sodium benzoate, sodium lauryl sulfate, sodium saccharin, calcium carbonate, peppermint, distilled water, clove oil with variations in the addition of concentrations of 1%, 2%, 3%, and 4%. The synthesis results produced a toothpaste preparation made from hydroxyapatite-nanosilver-clove oil, as evidenced by the results of FTIR characterization showing the presence of OH-, CO32-, PO43-, C-H, C-O, and C=O functional groups. PSA results show hydroxyapatite-nanosilver-clove oil has an average size of 4464 nm which is not included in the nanoparticle category (<100 nm). The toothpaste spreadability test resulted in a spread diameter of 5-6 cm, which met the requirements for paste spreadability (5-7 cm), while the adhesion test resulted in adhesion (7-12 seconds) which has not met the ideal requirements (1-6 seconds). The pH measurement resulted in a toothpaste pH of 8.8-9.0 per SNI (4.5-10.5). The homogeneity test of the toothpaste has met the requirements according to SNI, namely the absence of air bubbles, clumps, and separated particles. The antibacterial activity test showed that the hydroxyapatite-nanosilver-clove oil toothpaste formulation was able to inhibit the growth of S.mutans bacteria with the highest inhibition diameter in the variation of adding 4% concentration of clove oil, namely 14.99 mm with normally distributed data (p>0.05). One Way ANOVA statistical analysis showed that the treatment variation had a significantly different effect (p<0.05). These results indicate that adding clove oil into the formulation of hydroxyapatite-nanosilver-clove oil toothpaste can affect its chemical, physical, and antibacterial activity.